Tinjauan Yuridis Pengaturan Penyeberangan Sampan di Desa Pebenaan Kabupaten Indragiri dalam Perspektif Kewenangan Desa Menurut Undang-Undang Nomor 6 Tahun 2014 - Usman Usman; Jamri Jamri; Kms. Novyar Satriawan Fikri (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the implementation of the Village Consultative Body’s (BPD) authority to propose the dismissal of the Village Head in Pebenaan Village, Indragiri Hilir Regency, based on Law Number 6 of 2014 concerning Villages. It also analyzes factors influencing this authority and its compliance with applicable regulations. Using empirical legal research with a sociological approach, data were collected through interviews with BPD members and the Village Head, supported by legal literature analysis. The findings show that the BPD’s proposal to dismiss the Village Head represents a supervisory function in village governance. However, its implementation is influenced by village financial transparency, accountability, community pressure, political dynamics, and limited understanding of legal authority boundaries. The proposal to appoint an Acting Village Head before an official dismissal decision by the Regent indicates inconsistency with the principle of legality and existing legal provisions.